Demonstrating public health impacts of translational science at the clinical and translational science collaborative (CTSC) of northern Ohio: a mixed-methods approach using the translational science benefits model - Zhang, Lixin; Gurkan, Umut A.; Qua, Kelli; Swiatkowski, Shannon; Hemphill, Sheree; Pelfrey, Clara M. (Frontiers in Public Health, 2025)
The Clinical and Translational Science Award (CTSA) program, funded by the National Center for Advancing Translational Sciences (NCATS), aims to accelerate the translation of research into public health impacts. However, measuring the societal impact of translational research poses challenges due to extended timelines for implementation. This study uses the Translational Science Benefits Model (TSBM) to evaluate the societal impact of CTSA-supported research at the Clinical and Translational Science Collaborative (CTSC) of Northern Ohio at Case Western Reserve University (CWRU). Using the TSBM, we asked how investigators have used the CTSC to demonstrate translational science impacts in public health practice both domestically and internationally. Using a mixed methods approach, this study analyzed TSBM-based survey data from CTSC-supported KL2 Scholars and Pilot Program awardees, along with key publications and interviews, to document societal benefits across four TSBM domains: Clinical & Medical, Community & Public Health, Economic, and Policy & Legislative. Findings demonstrate that CTSC-supported research improved public health by enhancing healthcare access, improving health outcomes, informing policy, and generating economic benefits. These impacts span local, national, and global contexts. By applying a mixed methods approach, we demonstrate the value of using the TSBM not just as an evaluative framework, but as a strategic tool for capturing the real-world significance of translational science. This approach strengthens the ability of CTSA hubs to highlight the broader public value of their work, reinforcing the CTSA program’s mission to transform scientific discoveries into lasting health and societal benefits.